Interventional pulmonology for patients with central airway obstruction: An 8-year institutional experience. Issue 2 (January 2017) - Chen, Chia-Hung; Wu, Biing-Ru; Cheng, Wen-Chien; Chen, Chih-Yu; Chen, Wei-Chun; Hsia, Te-Chun; Liao, Wei-Chih; Tu, Chih-Yen; Hsu, Wu-Huei
Abstract : Abstract: Patients with central airway obstruction (CAO) may need endobronchial intervention to relieve their symptoms. This report is on a single-center experience of using interventional bronchoscopy in terms of complications and survival. This retrospective study was conducted in a university hospital and involved 614 patients (464 men, 150 women; mean age, 60.2 years) with benign (n = 133) and malignant (n = 481) tracheobronchial disease who received 756 endobronchial intervention procedure during the period 2008 to 2015. Survival was analyzed using the Kaplan–Meier method, while the log-rank test was used for comparisons. A total of 583 patients (95%) achieved endoscopic success after interventional bronchoscopy. Four (0.7%) died within 24 hours of the procedure, while the major morbidities were halitosis (n = 41, 6.7%) and iatrogenic pneumonia (n = 24, 3.9%). Repeat procedures due to recurrent airway obstruction were done on 45 patients with benign conditions and on 60 with malignancies. The median survival after the procedure in patients with lung cancer, other metastatic cancer, and esophageal cancer was 166, 228, and 86 days, respectively. Between patients with inoperable lung cancer and CAO after therapeutic bronchoscopy and patients without CAO, there was no statistically significant difference in survival ( P = 0.101). Interventional bronchoscopy is a safe and effective procedure that may be recommended for CAO. Patients with lung metastases have similar lengths of survival as patients with primary lung cancer. Patients with advanced lung cancer and CAO have similar survival as those without CAO.